Invasive Group B Streptococcal disease in newborns at Groote Schuur Hospital - Browne, Bradley (Department of Paediatrics and Child Health, 2024)
Background. Group B Streptococcal disease is an important cause of morbidity and mortality in newborns globally, and is more common in Sub-Saharan Africa and South Africa. There are few studies reporting on the burden of invasive Group B Streptococcus disease (iGBS) in newborns in South Africa, especially in the Western Cape. Objective. This study aims to describe a case series of newborns with iGBS in a tertiary hospital in the Western Cape. Methods. A retrospective folder review was conducted between January 2015 and December 2020. Results. Thirty five cases of invasive GBS disease were included in the study, 51% with earlyonset disease (EoD) and 49% with late-onset disease (LoD). The median gestational age at birth was 27 and 31.5 weeks in the LoD and EoD groups respectively. The median birth weight was 900 g and 1812 g in the LoD and EoD group respectively. Meningits was more common in the LoD group, and pneumonia more common in the EoD group. The overall mortality rate was 23%, and GBS disease accounted for a cumulative 274 days in the intensive care unit. Conclusion. Invasive GBS disease in newborns at GSH carries a high mortality rate with a similar burden of LoD and EoD. More studies of newborn iGBS are needed in the Western Cape and South Africa to better understand the burden of disease.